Market proximity and irrigation infrastructure determine farmland rentals in Sichuan Province, China. (August 2022) - Leimer, Kristin; Levers, Christian; Sun, Zhanli; Müller, Daniel
Abstract: A dynamic market for farmland transactions can contribute to an increase in average farm size and to realising economies of scale in farming. China, with more than 200 million small and fragmented farms, has launched a new wave of land tenure reforms that foster land transfers to increase farm size and to improve agricultural efficiency. However, the factors that influence farmland transactions are far from clear. We aim to understand farmland rental determinants in response to a pilot land reform project in China's south-west Sichuan Province. We collected survey data from 410 farm households and used boosted regression trees to quantify the determinants of the land rentals. Our analyses provide three key findings. First, households with more plots equipped with irrigation infrastructure and closer distances to the nearest town were more likely to rent out land. Second, households rented out a larger share of their land when they had more irrigation infrastructure and lived close to Chengdu, the province capital. Third, the land reform pilot provided a modest but positive stimulus for land rentals. In sum, our results suggest that the supply and demand for land crucially hinges upon plot location and plot infrastructure. Highlights: We used household survey data to analyse land rentals with boosted regression trees. Rental transactions are higher for households that reside closer to the markets. Plots equipped for irrigation are more likely to be rented out. The impact of the land reform pilot likely provided a modest stimulus for farmland rentals.